Progressive dehydration causes a progressive decline in basketball skill performance - Baker, L. B.; Dougherty, K. A.; Chow, M.; Kenney, W. L. (Medicine & Science in Sports & Exercise, 2007)
Purpose: To determine the effect of 1, 2, 3, and 4% dehydration (DEH) versus euhydration (EUH) on basketball performance in adult male players.